The fractures of e-type fastening clips used in the subway: Theory and experiment. (November 2017) - Xiao, Hong; Wang, Jia-Bin; Zhang, Yan-Rong
Abstract: With the vigorous developments in urban rail transport systems of China, the fractures of fasteners have been frequently found in some newly built routes. This could aggravate the repair and maintenance apart from direct reduction in the operational safety. In this study, the fractures of fastener were systematically investigated with an aim of revealing the fracture mechanism and proposing effective repairing methods. Firstly, a refinement model of fastener was established. Based on the model, static analysis and dynamic analysis were carried out on the fastening clip. The static analysis is used to analyze the stress and strain by using the non-linear contact theory, and the dynamic analysis is used to analyze the vibration mode and harmonic response in the service state. Moreover, the static and dynamic on-site tests were also conducted on a typical route section. Results show that the stress concentration in fastening clips caused by the unreasonable installation in the term of excessive inserting depths and the vibration fastener resonance resulting from the rail corrugation as well as its second-order natural frequency led to the fracture. Highlights: The refinement model established in real size is used in the analysis rather than hypothesized and simplified model. Static and dynamic methods combine on-site tests to analysis the fracture mechanism. The stress concentration caused by unreasonable installation is one of the main fracture reasons. The resonance caused by the rail corrugation lead to the fractures of fastener.